Estrategias educomunicacionales para innovar la práctica del docente orientador en la institución educativa departamental técnica nueva granada de Magdalena, Colombia (2022)
The main objective of this research was to design educommunication strategies to innovate the work of the teacher as a counselor. The methodology used was qualitative, descriptive, diagnostic and propositional, from the perspective of the dialogic paradigm; for which a few moments were designed, configured in 4 phases; Direct observation, documentary review and in depth interviews were used to achieve the established purposes, applied to 2 directors, 1 student, 2 parents and 5 teachers. From the dialogic educommunication notion, a series of categories emerged on the practice of the guidance teacher, which were characterized by educational sessions in two analysis matrices: by composition and atomic. The fundamental contribution of the study is constituted by a set of 10 guidelines, which guided the formulation of the strategies that were specified in the construction of two mapping with the key elements to strengthen the guiding teaching practice (PDO).